GenAI: Giga$$$, TeraWatt-Hours, and GigaTons of CO. - Chien, Andrew A. (Communications of the ACM, 2023)
This article reports on the environmental impacts of generative artificial intelligence (AI). Topics include the rise in demand for generative AI hardware, including graphics processing units (GPUs), as well as analysis on power consumption and carbon emissions based on the rise in generative AI usage.